Wiley Encyclopedia of Management 2015
DOI: 10.1002/9781118785317.weom070047
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model And The Unified Theory Of Acceptance And Use Of Technology

Abstract: This article presents an overview of the unified theory of acceptance and use of technology. I trace its origins, which relates back to the technology acceptance model, and discuss related models. I share some of my experiences, as an author, editor, and reviewer, to identify some common problems in current research investigations in this area. Drawing on these lessons, I make suggestions for future research on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
374
4
53

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(450 citation statements)
references
References 29 publications
19
374
4
53
Order By: Relevance
“…The previous models were able to successfully predict the acceptance of an innovation for about 40% (Davis, 1989). However, UTAUT can account for an impressive 70% of the variance in behavioral intention and about 50% in actual usage (Venkatesh et al, 2012).…”
Section: Virtual Community (Vc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The previous models were able to successfully predict the acceptance of an innovation for about 40% (Davis, 1989). However, UTAUT can account for an impressive 70% of the variance in behavioral intention and about 50% in actual usage (Venkatesh et al, 2012).…”
Section: Virtual Community (Vc)mentioning
confidence: 99%
“…Davis (1989) indicated that these models could successfully predict the acceptance of an innovation at about 40%. Superior to these models is the Unified Theory of Acceptance and Use of Technology model (UTAUT), a technology innovation acceptance model that can account for an impressive 70% of the variance in behavioral intention and 50% of actual usage (Venkatesh, Thong, & Xu, 2012). Thus, the authors of this study were motivated to use UTAUT as the theoretical framework to conduct an empirical study using cosmetic-related VC (an IT-based and self-supported business application) as the research context.…”
Section: Introductionmentioning
confidence: 99%
“…Venkatesh et al, [48] mentioned that the use of mixed method approach (ie. to use both qualitative and quantitative) in IS field is lack.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of inferences from qualitative and quantitative studies will contribute greatly to the process of developing high quality meta-inferences [48]. Meta-inferences is defined as theoretical statements, narratives or a story inferred from an integration of findings from mixed method approach [48]. Onwuegbuzie and Johnson [49] have identified nine new types of legitimation that come to the fore as a result of combining inferences from the quantitative and qualitative components of a mixed research study to form meta-inferences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation